Perancangan E-Marketplace Sewa-Menyewa sebagai Alternatif Bisnis di Era Digital - David Christian Aditya Gunadi; Teddy Marcus Zakaria (Maranatha University Press, 2018)
In our life, there is often a need that is only temporary. Most have many main needs that must be met. If they need an item that is used in the short term, they borrow from friends and neighbors rather than buying the item. On the other hand, if they have items, which want to be used to earn additional income, it can be lent to earn income. The development of internet technology will affect the pattern of life such as rent-lease, sales-buy or other businesses. The electronic marketplace became an alternative for today. E-marketplace is a container to unify sellers and buyers according to their needs because it offers ease in transactions. E-marketplace of rent-lease becomes necessary to meet temporary needs. The purpose of E-marketplace is to help tenants and owners of goods to increase the value of leased goods. The objective of this study is to design Web-based Information System as a container where rent transactions can run online. The owner can offer the goods, the tenant can rent the items needed, pay and return the items that have been rented. Admin acts as a mediator for payment processing.